Monopolistic Competition, Risk Aversion, and Equilibrium Recessions - Frank, Jeff (Quarterly Journal of Economics, 1990)
This paper considers a model with monopolistic competition and multiple equilibria, rankable by output, employment, and the Pareto criterion. While papers in the literature assume a linear production technology and derive a continuum of equilibria, we assume a standard diminishing returns production function and find a finite set of equilibria. Our new feature is the assumption that firms behave in a risk-averse manner. A low-level equilibrium is sustainable because firms, at the low profits level associated with the equilibrium, become extremely cautious in their employment decisions.